Readiness and Intention for Adapting New Normal COVID-19 Prevention Campaign for Sustainable Response Among Debre Berhan University Student’s During Campus Re-Entry: A Cross-Sectional Study - Taye, Birhan Tsegaw; Mihret, Muhabaw Shumye; Tiguh, Agumas Eskezia; Dinberu, Mesfin Tadese; Kitaw, Tebabere Moltot; Tessema, Saba Desta; Zerihun, Mulualem Silesh; Haile, Asalif Beyene; Worku, Solomon Adanew; Amogne, Fetene Kasahun; Amare, Nakachew Sewnet; Demisse, Tesfanesh Lemma; et al. (Frontiers in Education, 2021)
Background: The COVID-19 pandemic has had a profound effect on the general healthcare system and higher education worldwide. Adapting to the culture of “new normal,” an emerging response to COVID-19, is crucial for public health recovery and learning. This study investigated students' readiness and intention for adapting to the ‘‘new normal’’ COVID-19 prevention campaign during campus re-entry in Debre Berhan university in Ethiopia after the country eases lockdown restrictions. Methods: A cross-sectional study was conducted from 20th to 30th January 2021, among graduate students in Debre Berhan university, Ethiopia. A simple random sampling technique was used to select 423 participants. A structured and pre-tested self-administered questionnaire was used to collect the data and bivariate and multivariable logistic regressions were fitted. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) were used to interpret the strength of association and the statistical significance level was declared at a p-value of ≤0.05. Result: In this study 423 participants were involved. The level of readiness and intention of adapting to the ‘‘new normal’’ prevention campaign were 49.4 and 54.8% respectively. Being a health science student (AOR = 1.82; 95% CI: 1.18, 2.81), being married (AOR = 2.10; 95% CI: 1.1, 4.05), having a smartphone (AOR = 1.84; 95% CI: 1.09, 3.12), and being knowledgeable towards COVID-19 (AOR = 1.56; 95% CI: 1.04, 2.34) were found to be significant factors associated with intention towards adapting to the ‘‘new normal’’ prevention practice. Also, the main reason why participants had no intention to carry out the ‘‘new normal’’ prevention campaign were a shortage of quality required preventive supplies (60%) and those who perceived themselves personally not at risk of COVID-19 (31.3%). Conclusion: In this study, although information on the COVID-19 outbreak is continually evolving, readiness and intention for adapting to the ‘‘new normal’’ COVID-19 prevention campaign were insufficient. It is critical to improve readiness and intention through increasing knowledge and emphasizing the importance of new technologies and handy protective supplies that may encourage the sustainable practice of new norms post-pandemic.